Preclinical evidence for luteolin in ulcerative colitis: a meta-analysis and systematic review - Feng, Yiyi; Lu, Xingyao; Guo, Enjia; Mo, Jianling; Xv, Yichuan (Frontiers in Pharmacology, 2025)
BackgroundEvidence suggests that luteolin (LUT) may offer therapeutic potential in treating ulcerative colitis (UC), though its specific pharmacological mechanisms remain incompletely understood. This meta-analysis aims to assess the pharmacological effects of LUT in UC animal models and investigate its potential mechanisms of action.MethodsA comprehensive search of five databases, namely, PubMed, Web of Science, Embase, EBSCO, and ScienceDirect, was conducted to identify studies investigating the effects of LUT on UC. The search, covering data up to March 2025, yielded 19 eligible studies involving a total of 327 animal subjects. The outcomes were analyzed using the standard mean difference with a 95% confidence interval in R (4.3.3) software.ResultsThe meta-analysis revealed that LUT significantly ameliorated colon length, reduced the disease activity index, alleviated body weight loss, and decreased histological scores. Further mechanistic analysis indicated that LUT exerts its effects through multiple mechanisms, including the reduction of pro-inflammatory cytokines, elevation of anti-inflammatory cytokines, promotion of tight junction protein expression, and improvement of oxidative stress-related indices. However, LUT appears to have no significant impact on the α-diversity of the intestinal microbiota.ConclusionThis study suggests that LUT may exert significant therapeutic effects in UC animal models through antioxidant, anti-inflammatory, immunomodulatory, and barrier-protective mechanisms. Further clinical studies and translational research are essential to bridge the gap between animal models and human applications.Systematic Review Registrationhttps://inplasy.com/inplasy-2025-5-0055/, identifier INPLASY202550055.